2020
DOI: 10.3389/fnins.2020.559077
|View full text |Cite
|
Sign up to set email alerts
|

Basal Forebrain Cholinergic Activity Modulates Isoflurane and Propofol Anesthesia

Abstract: Cholinergic neurons in the basal forebrain (BF) have long been considered to be the key neurons in the regulation of cortical and behavioral arousal, and cholinergic activation in the downstream region of the BF can arouse anesthetized rats. However, whether the activation of BF cholinergic neurons can induce behavior and electroencephalogram (EEG) recovery from anesthesia is unclear. In this study, based on a transgenic mouse line expressing ChAT-IRES-Cre, we applied a fiber photometry system combined with GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 51 publications
5
38
1
Order By: Relevance
“…Simultaneously filtered at 40 Hz and digitalized at 500 Hz. An optical fiber (Newton Inc., China) integrated with an optical diverter (Doric Lenses) was used to transmit the light between the fiber photometry system and the implanted optical fiber ( Luo et al, 2018 , 2020 ; Liu et al, 2020a ; Xu et al, 2020 ). One month later, 12 mice were subjected to record changes in GCaMP signals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously filtered at 40 Hz and digitalized at 500 Hz. An optical fiber (Newton Inc., China) integrated with an optical diverter (Doric Lenses) was used to transmit the light between the fiber photometry system and the implanted optical fiber ( Luo et al, 2018 , 2020 ; Liu et al, 2020a ; Xu et al, 2020 ). One month later, 12 mice were subjected to record changes in GCaMP signals.…”
Section: Methodsmentioning
confidence: 99%
“…Fiber photometry data were analyzed using MATLAB 2016a (MathWorks, Cambridge, United States). The values of fluorescence change (Δ F / F ) were calculated using the following formula: ( F − F 0 )/ F 0 , where F is the test fluorescence signal and F 0 is the basal signal ( Luo et al, 2018 , 2020 ; Liu et al, 2020a ; Xu et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that brain regions that regulate arousal become active during anesthesia recovery process ( Muindi et al, 2016 ; Luo et al, 2018 ; Luo et al, 2020 ). Additionally, the histaminergic ( Luo and Leung, 2009 ), cholinergic ( Irmak and de Lecea, 2014 ), noradrenergic ( Berridge et al, 2012 ; Fu et al, 2017 ), dopaminergic ( Eban-Rothschild et al, 2016 ; Taylor et al, 2016 ), and orexinergic pathways ( Sakurai, 2007 ) have been implicated in linking sleep-wake regulation and the emergence from GA. Our c-Fos immunostaining data reveals that LC TH neurons are active during emergence from isoflurane anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation may trigger cognitive dysfunction after surgery via synaptic dysfunction, neuronal cell death, and microglial priming (Lyman et al, 2014); Aβ accumulation and neuroinflammation mutually enhance neurotoxicity (Yamamoto et al, 2007;Wan et al, 2010). General anesthesia per se (induced by inhaled anesthetics) increased Aβ production and aggregation, and tau accumulation (Run et al, 2009;Perucho et al, 2010), and inhibited the activities of cholinergic neurons in preclinical studies (Luo et al, 2020). However, clinical studies found no evidence that general anesthesia increased POCD, compared to non-general anesthesia (neuraxial, regional and local anesthesia; Mason et al, 2010;Silbert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%